2008
DOI: 10.1190/1.2978166
|View full text |Cite
|
Sign up to set email alerts
|

Gravimetric monitoring of gas production from the Troll field

Abstract: Three surveys of relative gravity and depth measurements have been carried out over the Troll field during gas production. Due to several improvements in the methodology, precision (intra-survey repeatability measured as standard deviation) has i mproved from 26 µGal to 11 µGal and 4 µGal in the latest survey. This will improve the reliability of future monitoring, and also opens the range of applications to smaller and deeper fields.There is no clear subsidence of the seafloor. The estimated average depth cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…It is possible that, once embedded in the sediment, seafloor benchmarks are quite stable. Hundreds of concrete benchmarks have been placed on the bottom of the North Sea for geodetic monitoring of deformation associated with natural gas production and, at least at the 5-mm level, their vertical positions are quite stable over many years (Eiken et al, 2008;Stenvold et al, 2006). It remains to be seen how stable the endpoints of a long-baseline strainmeter can be when attached to deep ocean sediment.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that, once embedded in the sediment, seafloor benchmarks are quite stable. Hundreds of concrete benchmarks have been placed on the bottom of the North Sea for geodetic monitoring of deformation associated with natural gas production and, at least at the 5-mm level, their vertical positions are quite stable over many years (Eiken et al, 2008;Stenvold et al, 2006). It remains to be seen how stable the endpoints of a long-baseline strainmeter can be when attached to deep ocean sediment.…”
Section: Introductionmentioning
confidence: 99%
“…El Ouair et al (2005) and Buland and El Ouair (2006) further the concept of difference inversion. They use a Bayesian framework along with information from the expected elasticproperty changes and the measured seismic repeatability to provide uncertainty estimates for the impedance change.…”
mentioning
confidence: 99%
“…Time-lapse gravimetry has been used extensively in oil and gas production monitoring (e.g., Alnes et al, 2008;Brady et al, 2008;Eiken et al, 2008;Ferguson et al, 2008;Alnes et al, 2011;Dodds et al, 2013) and in groundwater and aquifer studies (e.g., Cogbill et al, 2006;Davis et al, 2008;Gehman et al, 2009). A more comprehensive review can be found in Krahenbuhl and Li (2012).…”
Section: Time-lapse Gravity and Gravity Gradiometrymentioning
confidence: 99%